Relationship Between Pregnancy-Associated Malaria and Adverse Pregnancy Outcomes: a Systematic Review and Meta-Analysis. (10th October 2019) - Thompson, Julie M; Eick, Stephanie M; Dailey, Cody; Dale, Ariella P; Mehta, Mansi; Nair, Anjali; Cordero, José F; Welton, Michael
Abstract: Background: Pregnancy-associated malaria (PAM) has been associated with adverse pregnancy outcomes like preterm birth (PTB) and low birthweight (LBW), which are among the leading causes of infant mortality globally. Rates of PTB and LBW are high in countries with a high burden of malaria. PAM may be a contributing factor to PTB and LBW, but is not well understood. Methods: We conducted a systematic review and meta-analysis of studies examining the relationship between PAM and PTB or LBW using PubMed. The title and abstract of all studies were screened by two reviewers, and the full text of selected studies was reviewed to ensure they met inclusion criteria. Information regarding study characteristics and of PTB and LBW births among women with and without PAM was abstracted for included studies. Results: Our search terms yielded 2237 articles, of which 18 met our final inclusion criteria. Eight studies examined associations between PAM and PTB, and 10 examined associations between PAM and LBW (population size ranging from 35 to 9956 women). The overall risk of LBW was 63% higher among women with PAM compared with women without PAM (95% CI = 1.48–1.80) and the risk of PTB was 23% higher among women with PAM compared with women without PAM (95% CI = 1.07–1.41). Conclusions: These results indicate that infection with PAM is associated with PTB and LBW. Further understanding of the pathogenesis of disease and the immunologic changes that occur during pregnancy is essential for reducing the disproportional effects this disease has on this vulnerable population.